SISTEM INFORMASI ANTREAN BERBASIS WEB DAN LED MATRIX DISPLAY - Zulkarnaen, Zulkarnaen; Nizar Mukhsin (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2023)
Queues are often encountered in daily activities. The queuing process is a process related to the arrival of customers at a service facility, waiting to get service until they finally get service and leave the service facility. Many queue models use single-server, single-phase system and multiple-server, single-phase system. Currently, there are still service facilities that have not utilized technology to provide convenience for the users. One way to improve service quality is by using a queuing system. The method applied in building this system is Prototype method. The prototype method consists of communication, which is the stage of data collection through the method of literature, observation, experiments which are described in use cases, activity and sequence diagrams as well as device requirements. Modeling Quick Design is the stage of making a brief description of the design in the form of architecture and appearance design. Construction of Prototype is the design stage, built using PHP MVC, MySQL, C++, JavaScript, JSON, NodeMCU ESP8266 microcontroller as a link for each device via a Wi-Fi network as well as a P10 led matrix display controller. P10 led matrix and monitor displays the queue number. The web server installed on the PC acts as a center for managing queue numbers, queue voice calls via text to speech as a voice generator in the Edge browser. Deployment Delivery & Feedback are the testing stages. the results obtained are to produce a web-based queue number information system and led matrix display that has been tested using black box testing that this system can run well